Exploration of Students' Clinical Reasoning Development in Professional Physical Therapy Education. Issue 3 (2015) - Furze, Jennifer; Black, Lisa; Hoffman, Julie; Barr, J B; Cochran, Teresa M.; Jensen, Gail M.
Abstract : Background and Purpose. : Given the complexity of the current health care environment, effective clinical reasoning skills are fundamental to making critical patient care decisions. The purpose of this study was to explore the clinical reasoning abilities of students across time in 1 professional Doctor of Physical Therapy (DPT) curriculum. Methods. : Qualitative methods were used to describe the longitudinal development of students' clinical reasoning skills. Ninety‐eight students from 2 consecutive class cohorts participated. Low inference data from the Clinical Reasoning Reflection Questionnaire (CRRQ) and narrative comments from the Clinical Performance Instrument (CPI) were analyzed using the constant comparative method. Open coding was used to initially categorize the data followed by axial coding to identify resulting themes. Results. : Three categories (beginning, intermediate, and entry‐level) and 8 themes emerged from the data describing student development of clinical reasoning skills. The following themes surfaced under the beginning clinical reasoning process category: focus on self, compartmentalized thinking, and limited acceptance of responsibility. Themes in the intermediate category were: procedural performance, initial stages of recognition and using context, and improved reflection on performance. Themes in the final entry‐level category were: dynamic patient interaction and integrating situational awareness. Discussion and Conclusion. : The results of this study demonstrate a progression in the development of these students' clinical reasoning process around the dimensions of self, context, and responsibility across the curriculum. Outcomes reveal these key aspects of the clinical reasoning process: (1) it is a gradual developmental process across time; (2) the Dreyfus model of skill acquisition may apply to the development of clinical reasoning skills in physical therapy students; and (3) increasing intensity and depth of the reflective process may be a critical component in the advancement of the clinical reasoning process. Further research is needed to determine the best strategies to assess clinical reasoning abilities in physical therapy students and to discern approaches to enhance this learning process.